Changes in the level of oxidative stress markers in Indian catfish (Wallago attu) infected with Isoparorchis hypselobagri - Anam Sahreen (SpringerOpen, 2021)
Abstract Background Helminth infection and infestation in fishes are detrimental and have a major effect on fish health and fish production. Among various factors, parasitic infections are known to modulate antioxidant defences in fish. Similar to other aerobic animals, fish are also susceptible to the effect of reactive oxygen species and thus have well established intrinsic and efficient antioxidant defences. ‘Oxidative stress markers are an important indicator of the physiological state of the parasite and its host’. Indian catfish, Wallago attu is a freshwater fish that serves as the definitive host of the adult piscine trematode Isoparorchis hypselobagri. Our two years prevalence data signifies the intensity of the problem revealing a minimum of 5.5% and a maximum of 54% I. hypselobagri infection in Indian catfish W. attu (unpublished data). The present study aimed to achieve baseline data attributed to changes in some oxidative markers due to parasitic infection. Results During the present study, the level of enzyme activities of Catalase (CAT), Glutathione reductase (GR), Glutathione-S-transferase (GST), Glutathione peroxidase (GPx), Superoxide dismutase (SOD) and lipid peroxidation was investigated to explore the pathogenic impact on the fish host. The level of these oxidative stress markers was monitored in the swim bladder, liver, intestine and muscle of the host. We also recorded the enzyme activities in the parasite I. hypselobagri. Analysis of data revealed an elevation in GST, SOD, GR, GPx and CAT activity in the infected host tissue as compared to the non-infected fish. Further, we observed presence of GST, SOD, GR and GPx enzymes in the parasite I. hypselobagri while CAT did not show any enzyme activity. Conclusions Increased level of enzyme activity in liver, muscle and intestine of infected host has been recorded which indicates increased oxidative stress in the host due to parasitic invasion. The presence of antioxidant enzymes in the parasites suggests an active antioxidant defence system to avoid immune responses to long term survival and establishment in their host.